Pioneering Robotic Liver Surgery in Germany: First Experiences with Liver Malignancies - Croner, Roland S.; Perrakis, Aristotelis; Brunner, Maximillian; Matzel, Klaus E.; Hohenberger, Werner (Frontiers in Surgery, 2015)
Background: Minimally invasive liver surgery is growing worldwide with obvious benefits for the treated patients. These procedures maybe improved by robotic techniques which add several innovative features. In Germany we were the first surgical department implementing robotic assisted minimally invasive liver resections. Material and Methods: Between June 2013 and March 2015 we performed robotic based minimally invasive liver resections in 9 patients with malignant liver disease. Five off these patients suffered from primary and 4 from secondary liver malignancies. We retrospectively analyzed the perioperative variables of these patients and the oncological follow up. Results: Mean age of the patients was 63 years (range 45-71). One patient suffered from intrahepatic cholangiocellular and 4 from hepatocellular carcinoma, 4 patients from colorectal liver metastases. In six patients left lateral liver resection and in two cases single segment resection and in one case minimally invasive guided liver ablation was performed. Five patients underwent previous abdominal surgery. Mean operation time was 312 min (range 115-458 min). Mean weight of the liver specimens was 182g (range 62-260 g) and mean estimated blood loss was 251 ml (range 10-650 ml). The mean tumor size was 4.4 cm (range 3.5-5.5 cm). In all cases R0 status was confirmed with a mean margin of 0.6 cm (range 0.1-1.5 cm). One patient developed small bowel fistula on postoperative day 5 which could be treated conservatively. No patient died. Mean hospital stay of the patients was 6 days (range 3-10 days). During a mean follow up of 12 month (range 1-21 month) two patients developed tumor recurrence. Conclusion: Robotic based liver surgery is feasible in patients with primary and secondary liver malignancies. To achieve perioperative parameters comparable to open settings the learning curve must be passed. Minor liver resections are good candidates to start this technique. But the huge benefits of